From accounting to accountability: social and relational accountability among civic humanitarian actors in Uganda - Emmanuel Viga; Hilde Refstie (Fennia: International Journal of Geography)
This article examines how accountability is understood and practiced in refugee and community led assistance among South Sudanese refugees in Uganda. Although the humanitarian localisation agenda advocates greater support for local actors, accountability remains contested and complex. Dominant frameworks emphasise formal mechanisms such as reporting, audits, and compliance with donor requirements, rooted in a technomanagerial logic of control and risk management. By constrast, this article highlights how accountability is enacted through informal, socially embedded practices shaped by soft power, collective expectations, social standing, and relational responsibilities. Drawing on ethnographic fieldwork conducted between 2020 and 2023, it explores accountability as it emerges in diaspora networks, community leadership, familial and neighborly assistance, and communal practices. The analysis is grounded in four main bodies of literature: African relational philosophies such as Ubuntu, scholarship on socialising forms of accountability, decolonial critiques of humanitarian governance, and literature on community driven development. Together, they offer a framework for understanding accountability not only as technomanagerial procedures, but as a dynamic, negotiated social process. Through ethnographic vignettes, the article shows that relational and technomanagerial forms of accountability are not necessarily opposites or mutually exclusive, but operate with different logics. This has implications for the humanitarian localisation agenda: when community and refugee led accountability is made legible to international actors, informal relational practices are often turned into formal indicators, distorting local meanings and reinforcing hierarchies. The article calls for redefining accountability in humanitarianism as a process attentive to context, culture, relationships, and lived experience.